Prognostic Relevance of CCDC88C (Daple) Transcripts in the Peripheral Blood of Patients with Cutaneous Melanoma. Issue 1 (December 2018) - Dunkel, Ying; Reid, Anna; Ear, Jason; Aznar, Nicolas; Millward, Michael; Gray, Elin; Pearce, Robert; Ziman, Melanie; Ghosh, Pradipta
Abstract A loss of balance between G protein activation and deactivation has been implicated in the initiation of melanomas, and non-canonical Wnt signaling via the Wnt5A/Frizzled (FZD) pathway has been shown to be critical for the switch to an invasive phenotype. Daple [CCDC88C], a cytosolic guanine nucleotide exchange modulator (GEM) which enhances non-canonical Wnt5A/FZD signaling via activation of trimeric G protein, Gαi, has been shown to serve opposing roles–as an inducer of EMT and invasiveness and a potent tumor suppressor–via two isoforms, V1 (full-length) and V2 (short spliced isoform), respectively. Here we report that the relative abundance of these isoforms in the peripheral circulation, presumably largely from circulating tumor cells (CTCs), is a prognostic marker of cutaneous melanomas. Expression of V1 is increased in both the early and late clinical stages (p < 0.001, p = 0.002, respectively); V2 is decreased exclusively in the late clinical stage (p = 0.003). The two isoforms have opposing prognostic effects: high expression of V2 increases relapse-free survival (RFS;p = 0.014), whereas high expression of V1 tends to decrease RFS (p = 0.051). Furthermore, these effects are additive, in that melanoma patients with a low V2-high V1 signature carry the highest risk of metastatic disease. We conclude that detection of Daple transcripts in the peripheral blood (i.e., liquid biopsies) of patients with melanoma may serve as a prognostic marker and an effective strategy for non-invasive long-term follow-up of patients with melanoma.